Pengaruh Komunikasi Interpersonal terhadap Kinerja Karyawan di Yayasan Matahari Banyuwangi - Suwardi, Suci Melati; Kurniawan, Firdaus Dwi Cahyo (Fakultas Dakwah UIN KHAS Jember, 2023)
This study aims to determine whether there is an effect of Interpersonal Communication on the Performance of Employees of the Matahari Banyuwangi Foundation and how much influence Interpersonal Communication has on the Performance of Employees of the Matahari Banyuwangi Foundation. This study uses quantitative methods. The sampling technique is a census technique or total sampling of 34 employees. Questionnaires or questionnaires are used as data collection techniques containing interpersonal communication scales and employee performance scales. Data analysis techniques in the form of descriptive statistical tests, categorization tests. Classical assumption tests, and simple linear regression tests. The results of this study can be known from the significance value or P value of 0.007 <0.05 (there is an influence). The results of this study can also be seen through the value of t count> t table, 2.911> 2.036. This means that the hypothesis Ha (there is an influence) is accepted and Ho (there is no influence) is rejected. Interpersonal communication also has a positive effect on employee performance, meaning that when interpersonal communication increases, employee performance also increases and vice versa. When interpersonal communication decreases, employee performance also decreases, and interpersonal communication has an effect of 20.9% on employee performance.